2018
DOI: 10.4103/ijpvm.ijpvm_484_17
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference as an indicator of central obesity in healthy young Bosnian Adults: Cross-sectional study

Abstract: Background:Neck circumference (NC) is an index of subcutaneous adipose tissue distribution in an area of the upper part of the body. The aim of this study was to assess whether NC can be used as an indicator of central obesity and to determine the prevalence of central obesity in apparently healthy Bosnian young adults.Methods:Participants for this cross-sectional study were recruited using the snowball method. NC was measured in horizontal straight position by placing the top edge of a plastic tape only below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“… 10 Some studies in adults have demonstrated a relationship between the measurement of neck circumference and anthropometric indexes used to measure obesity. 11 , 12 This relationship has also been observed in research involving children. 13 , 14 , 15 The theme has been gaining greater importance in recent years, but literature is still scarce.…”
Section: Introductionsupporting
confidence: 57%
“… 10 Some studies in adults have demonstrated a relationship between the measurement of neck circumference and anthropometric indexes used to measure obesity. 11 , 12 This relationship has also been observed in research involving children. 13 , 14 , 15 The theme has been gaining greater importance in recent years, but literature is still scarce.…”
Section: Introductionsupporting
confidence: 57%
“…Neck circumference (NC) has been suggested as an easily accessible and replicable anthropometric measurement to perform NAT evaluation [8], which has previously shown associations to body mass index (BMI) and VAT [9][10][11][12] and is also an independent risk factor for central obesity and metabolic disease [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However various other studies, conducted in different parts of the world, have proved that neck circumference is replaceable for waist circumference and is a simple and best measure of central obesity. 19,20…”
Section: Discussionmentioning
confidence: 99%